Multi-stakeholder consensus on a target product profile for an HIV cure. Issue 1 (January 2021) - Lewin, Sharon R; Attoye, Timothy; Bansbach, Cathy; Doehle, Brian; Dubé, Karine; Dybul, Mark; SenGupta, Devi; Jiang, Adam; Johnston, Rowena; Lamplough, Rosanne; McCune, Joseph M; Nabel, Gary J; et al.
Summary: Developing a cure for HIV is a global priority. Target product profiles are a tool commonly used throughout the drug development process to align interested parties around a clear set of goals or requirements for a potential product. Three distinct therapeutic modalities (combination therapies, ex-vivo gene therapy, and in-vivo gene therapy) for a target product profile for an HIV cure were identified. Using a process of expert face-to-face consultation and an online Delphi consultation, we found a high degree of agreement regarding the criteria for the optimum target product profile. Although the minimum attributes for a cure were debated, the broad consensus was that an acceptable cure need not be as safe and effective as optimally delivered antiretroviral therapy. An intervention that successfully cured a reasonable fraction of adults would be sufficient to advance to the clinic. These target product profiles will require further discussion and ongoing revisions as the field matures.